Sepak to a shared vision a study on the fantasy themes and rhetorical vision of the Philippine national sepak takraw team - Uy, Christian Joseph S.; Rodriguez, Marti S. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2019)
This study titled Sepak to a SHared Vision: A Study on the Fantasy Themes and Rhetorical Vision of the Philippine National Sepak Takraw team focused on extracting the vision of the athletes. The statement of the problem is "How does the symbolic convergence of the members of Philippine National Sepak Takraw Team reflect their rhetorical vision?" This problematique is further broken down into three objectives, namely to:1. Elicit the fantasy themes present in the Philippine National Sepak Takraw Team's narratives;2. Identify the elements of the fantasy themes present in the Philippine National Sepak Takraw Team's narratives;3. Examine the rhetorical vision reflected by the fantasy themes of the members of the Philippine National Sepak Takraw Team. These objectives were met via the use of data from participant observations, in-depth interviews, and focus group discussion. These methods elicited recurring patterns and themes from the narratives of the participants mostly on the identity of the team, such as their team as a family and as a support group. It also tackled stories regarding their shared moments together, their sacrifices and hardships, and their hopes for a better future for their team. From these fantasy themes, the most salient and frequently chained-out stories and fantasies of the participants formed a shared rhetorical vision. This vision was about the hopes of the athletes for a better future for their team and the sport in general. Moreover, the communication of the team manifested the presence of convergence in terms of their symbolic realities. This is discovered through their communication heavily reliant on imageries. It was also evident that the presence of similarities in terms of their utterances and overall understanding of things allowed for them to communicate their vision with everyone, even with me who is not a member of the team.
Thesis (B.A. in Speech Communication)--University of the Philippines Diliman
Includes bibliographical references and appendices.